1983
DOI: 10.1021/ja00350a031
|View full text |Cite
|
Sign up to set email alerts
|

Activation of carbon-hydrogen bonds in saturated hydrocarbons on photolysis of (.eta.5-C5Me5)(PMe3)IrH2. Relative rates of reaction of the intermediate with different types of carbon-hydrogen bonds and functionalization of the metal-bound alkyl groups

Abstract: 3929sealed at -196 OC. In preparation for each run, the tube was warmed to -78 OC in a C02/2-propanol bath with shaking to assure the complete formation of Sa. The tube was then warmed to room temperature and placed in the probe of an NMR spectrometer maintained at 28.0 f 0.5 OC. Data sets were collected over 3 half-lives of the reaction. A typical data set consisted of 12 acquisitions at 201.947 MHz with a SW = f1113.58 Hz, a pulse width of 20°, and a 5-s delay between pulses. The progress of the reaction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 363 publications
(121 citation statements)
references
References 0 publications
10
110
1
Order By: Relevance
“…As early as 1983 Bergman and Janowicz [7] found an approximate 1:1 ratio of the intra-and inter-molecular products in the reaction of [IrCp*(PR 3 )H 2 ] with hydrocarbons. Later Jones and Feher [8] investigated the selectivity of the phosphine cyclometallation vs. benzene activation by the [RhCp*(PCH 2 PhMe 2 )] system (this phosphine was chosen in order to have similar steric constraints for the inter-and intra-molecular pathways) finding out a moderately high thermodynamic preference for the intramolecular activation and a kinetic selectivity for the intermolecular reaction (in neat solvent).…”
Section: Reaction Energiesmentioning
confidence: 99%
“…As early as 1983 Bergman and Janowicz [7] found an approximate 1:1 ratio of the intra-and inter-molecular products in the reaction of [IrCp*(PR 3 )H 2 ] with hydrocarbons. Later Jones and Feher [8] investigated the selectivity of the phosphine cyclometallation vs. benzene activation by the [RhCp*(PCH 2 PhMe 2 )] system (this phosphine was chosen in order to have similar steric constraints for the inter-and intra-molecular pathways) finding out a moderately high thermodynamic preference for the intramolecular activation and a kinetic selectivity for the intermolecular reaction (in neat solvent).…”
Section: Reaction Energiesmentioning
confidence: 99%
“…Further investigations enabled the discovery of a "second generation" of this CDC reaction. It was found that polyhalogenated aromatics, such as hexabromobenzene, can be used as additives hence enabling the desired coupling with non-halogenated simple arenes and heteroaromatics (12) [141]. A closely related twofold C-H activation between one aromatic partner bearing a directing group and a second, heteroaromatic partner was discovered independently by You [142] and Kambe [143].…”
Section: C-h Activation By Metallacyclic Intermediatesmentioning
confidence: 99%
“…The reactivity of these pseudooctahedral complexes toward various ligands has been investigated enabling isolation and characterization of many interesting organometallic structures. Moreover, following the Maitlis work [11] and since the potential of [Cp*IrPR 3 X 2 ] and [Cp*RhPR 3 X 2 ] complexes to cleave C-H bonds [12,13] had been known already in the 1980s, an extensive study of the stoichiometric reactions between the dicationic [Cp*M(III)] precatalysts (M¼Rh, Ir) and aromatic substrates bearing coordinating substituents (such as imines, ketones, amines, etc.) was undertaken.…”
Section: Introduction and Background Of Organometallic Chemistrymentioning
confidence: 99%
“…The first involves the oxidative addition of the C-H bond to an unsaturated metal fragment, and is typical of electron-rich late metal systems [5][6][7][8][9][10][11][12][13]. The second takes place by a 1,2-R-H addition, in which the C-H bond adds across a highly electrophilic d o metal M-X bond [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Abstract: Iridium; C-h Activation; Metallacyclesmentioning
confidence: 99%